Banda de Congo Piabas/Irundi: Culture e Tradition - Martins de Oliveira, Marlene; Casotto Pirchiner, Juliana (Guará Journal, 2015)
This paper presents a project developed with the community leaders and the members of the “Banda de Congo” in two rural communities, providing aid to the celebrations, assisting the groups in governments cultural prizes, giving workshops, sensitizing and capacitating the leaders in conserve their cultural expressions. The effectiveness of the project happens by meetings, gatherings, interviews and workshops of the memories of Congo, photography and “toadas”, theirsfolk songs. They already achieved three prizes: The “Mestre Armojo do Folclore Capixaba” prize witch 1 awarded a king and a queen of “Banda de Congo”; The “Renato Pacheco” award to acquire adornments, costumes and musical instruments for the adults and childrento perform their presentations in theirs celebrations; both by the Secretary of Culture from the state of Espírito Santo; and, by the Secretary of Citizenship and Cultural Diversity from the federalMinistry of Culture; The “Cultura Populares - Edição 100 anos de Mazzaropi” prize for the “Banda de Congo”. By the maintenance and development of their culture for the future generations, preserving their immaterial cultural heritage we found the elevation of the “congueiros” self-esteems, creating a dwell environment for the exchange of knowledge and doings, strengthening the community bounds and the solidarity between the dwellers.
Keywords: Rural community; Banda de congo; Oral history; Immaterial patrimony; Assistance